A comparative study of the influence of alpha-lactose monohydrate particle morphology on granule and tablet properties after roll compaction/dry granulation. (16th March 2019) - Grote, Simon; Kleinebudde, Peter
Abstract: The influence of particle morphology and size of alpha-lactose monohydrate on dry granules and tablets was studied. Four different morphologies were investigated: Two grades of primary crystals, which differed in their particle size and structure (compact crystals vs. agglomerates). The materials were roll compacted at different specific compaction forces and changes in the particle size distribution and the specific surface area were measured. Afterwards, two fractions of granules were pressed to tablets and the tensile strength was compared to that from tablets compressed from the raw materials. The specific surface area was increased induced by roll compaction/dry granulation for all materials. At increased specific compaction forces, the materials showed sufficient size enlargement. The morphology of lactose determined the strength of direct compressed tablets. In contrast, the strength of granule tablets was leveled by the previous compression step during roll compaction/dry granulation. Thus, the tensile strength of tablets compressed directly from the powder mixtures determined whether materials exhibited a loss in tabletability after roll compaction/dry granulation or not. The granule size had only a slight influence on the strength of produced tablets. In some cases, the fraction of smaller granules showed a higher tensile strength compared to the larger fraction.